A reforma de base no ensino médio da história pátria: o projeto da história nova do Brasil - Guimarães, Lucia Maria Paschoal; Leonzo, Nanci (Revista de História, 2003)
This article examines the História Nova do Brasil project, a series of booklets published by the Ministry of Education and Culture through its Student Aid Campaign, on the eve of the 1964 military coup. Developed by specialists in the Higher Institute of Brazilian Studies (ISEB) and addressed to an audience of secondary teachers and students, the new series sought to revise the content of Brazilian history textbooks, by adopting a Marxist approach.